From eHealth to ePatient: The role of patient portals in fostering patient empowerment - Ammenwerth, Elske (European Journal for Biomedical Informatics, 2018)
Background: Health IT adoption is high in Austria, but health IT targeted at the patient is still rare. Objectives: To analyse the shift from eHealth to ePatient and the role that patient portals may have in this shift, from an Austrian perspective. Methods: Analysis of the situation in Austria regarding the use of eHealth and patient portals. Results: While eHealth applications are broadly used in Austria, only few applications address the patient as user and aim at facilitating patient empowerment. Patient portals are one approach to foster patient empowerment. In Austria, a national patient portal is introduced at the moment, but only with limited functionalities. Systematic reviews show that the evidence on the impact of patient portals on patient empowerment is still unclear, which may explain low adoption rates. It seems to be still a long way to support a new generation of ePatients who are equipped, enabled, empowered and engaged in their health and health care decisions. Conclusion: Patient portals and other eHealth interventions aiming at fostering patient empowerment can only show impact when health care professionals are willing to engage in a true partnership with the patient, and when patients are willing to take over responsibility for their own health management.
Keywords: Patient Portals; zapojení pacienta; telemedicína; portál pacienta; Austria; Humans; Telemedicine; Patient Participation; lidé; Rakousko